Design and Analysis of Logic Gates using GaN based Double Gate MOSFET (DG-MOS) - Arnub, Md Ibnul Bin Kader; Ali, M Tanseer (AIUB Journal of Science and Engineering (AJSE), 2018)
The double gate MOSFET, where two gates are fabricated along the length of the channel one after another. Design of logic gates is one of the most eminent application of Double Gate MOSFET. Gallium nitride (GaN) based metal-oxide semiconductor field-effect transistors (MOSFETs) are shown to be promising for digital logic applications. This paper describes the design and analysis of different types of logic gates using GaN based DG-MOSFET. The gate length (LG) is kept constant at 10.6 nm. The gate voltage varies from 0 to 1 V for the device switching from turn OFF to turn ON-state. For the device with HfO2 as gate oxide, the ON-state current (ION) and OFF-state current (IOFF) are found 8.11×10-3 and 6.38605×10-9A/µm respectively. The leakage current is low for the device with HfO2 as compared to that for the device with ZrO2. The subthreshold swing (SS) is 68.7408 mV/dec for the device with HfO2.